Late Talker Pada Anak Usia 3 Tahun: Parents Narration - Fitri Ramadhini; Lili Nur Indah Sari; Nashran Azizan (IAIN Padangsidimpuan, 2023)
Children generally go through distinct stages along the milestones of their language development, from crying, cooing, groping to mature speech. However, children with special conditions usually have difficulty passing through each phase of their development, such as those with expressive language disorders. These children usually have problems communicating their needs and ideas verbally and non-verbally. Through this research, the writer tries to present a narrative about the journey of the first three years of Sam, a child who has speech delays (late talker).Â Through interviews, observation, and documentation, this research informs that Sam experienced speech delays at the early stages of his language development and had difficulty constructing sentences with good grammatical arrangements.